Observatório ambiental para o PPGEDAM (NUMA/UFPA): a produção e divulgação do conhecimento em meio ambiente - LEDO, Ivaldo Ferreira (Universidade Federal do Pará, 2025)
Study of the production and dissemination of environmental knowledge and the applicability of products generated in graduate programs in the professional modality, based on the Graduate Program in Management of Natural Resources and Local Development in the Amazon (PPGEDAM). In this perspective, the general objective of the research is to propose the creation of an observatory for graduates of PPGEDAM/UFPA, for the visibility of environmental knowledge and technical-scientific products generated in the Program, contributing to local